Modelling main characteristics of fast neutron detector based on recoil protons with the Monte-Carlo method - Olejnik, S.N.; Bozhko, V.P.; Vodin, A.N. (Вопросы атомной науки и техники, 2002)
The program for calculation of amplitude spectra and fast neutron detector efficiency has been developed with the Monte-Carlo method (MC). The detector operates on the basis of the method of recoil protons and consists of a hydrogenous radiator and a Si surface-barrier counter of protons. Testing of the MC-program was carried out. Energetic and angular dependence of amplitude spectra and detector efficiency at neutron energy of 1-15MeV were calculated.